2014
DOI: 10.1007/s00068-014-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Trauma risk perception related to alcohol, cannabis, and cocaine intake

Abstract: The low perception of risk associated with alcohol, cannabis, or cocaine consumption by trauma patients under the influence of these substances on admission may be a predisposing factor for recidivism. Recommendations for both primary and secondary prevention are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Given that in our setting almost half of trauma patients are admitted under the influence of alcohol and/or illicit drugs [ 38 ], the potential impact on public health of the implementation of SBIRT programs in trauma centers in Spain is enormous. In a cost-benefit analysis [ 39 ] with a similar estimated trauma risk reduction, screening and brief intervention for alcohol problems in trauma patients was found to be cost-effective (savings of USD3.81 for every USD1.00 spent), and the authors suggested that it should be routinely implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that in our setting almost half of trauma patients are admitted under the influence of alcohol and/or illicit drugs [ 38 ], the potential impact on public health of the implementation of SBIRT programs in trauma centers in Spain is enormous. In a cost-benefit analysis [ 39 ] with a similar estimated trauma risk reduction, screening and brief intervention for alcohol problems in trauma patients was found to be cost-effective (savings of USD3.81 for every USD1.00 spent), and the authors suggested that it should be routinely implemented.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take into account that the reduction in alcohol and illicit drug use resulting from BI may not be the only mediator between BI and the reduction in trauma recidivism: BI may also have a positive influence on other variables causally related to trauma, such as impulsive behavior [ 40 46 ] or trauma risk perception related to substance use. This perceived risk is particularly low in our social context, especially among consumers of substances other than alcohol, such as cannabis and cocaine [ 38 ]. According to the authors of the DRUID project (DRiving Under the Influence of Drugs) carried out in 18 European countries [ 47 ], the greater likelihood observed in some countries of detecting drivers under the influence of illicit drugs and medicines compared to drivers exposed to alcohol may be explained by the lower efforts and resources devoted to campaigns for accident prevention related to the consumption of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been able to show an inverse relationship between the risk perception of the use of a particular harmful substance or drug (cannabis, alcohol, or tobacco) and the levels of use of that substance or drug in a social group [21,22,23,24]. However, concerning alcohol specifically and its consumption during pregnancy, there are very few studies exploring pregnant women’s risk perception and beliefs about the possible harmful effects of alcohol consumption during pregnancy [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increase in cannabis use and a decrease in the perception of the risk of consumption for health in general have been detected in our country [ 25 ]. We also find a low perception when cannabis users who have suffered trauma are asked about the perceived risk that consumption entails at the time of suffering road traffic injury [ 26 ].…”
Section: Discussionmentioning
confidence: 99%